Pediatric Fronto-Orbital Skull Reconstruction - Ferry, Andrew M.; Dibbs, Rami P.; Sarrami, Shayan M.; Abu-Ghname, Amjed; Beh, Han Zhuang; Maricevich, Renata S.; Buchanan, Edward P. (Facial Plastic Surgery, 2021)
Craniofacial surgery in children is a highly challenging discipline that requires extensive knowledge of craniofacial anatomy and pathology. Insults to the fronto-orbital skeleton have the potential to inflict significant morbidity and even mortality in patients due to its proximity to the central nervous system. In addition, significant aesthetic and ophthalmologic disturbances frequently accompany these insults. Craniosynostosis, facial trauma, and craniofacial tumors are all pathologies that frequently affect the fronto-orbital region of the craniofacial skeleton in children. While the mechanisms of these pathologies vary greatly, the underlying principles of reconstruction remain the same. Despite the limited data in certain areas of fronto-orbital reconstruction in children, significant innovations have greatly improved its safety and efficacy. It is imperative that further investigations of fronto-orbital reconstruction are undertaken so that craniofacial surgeons may provide optimal care for these patients.
Keywords: craniofacial surgery; fronto-orbital; craniosynostosis; reconstruction; pediatric